2019
DOI: 10.1111/acel.13064
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid receptor LPA3 prevents oxidative stress and cellular senescence in Hutchinson–Gilford progeria syndrome

Abstract: Hutchinson–Gilford progeria syndrome (HGPS) is a rare laminopathy that produces a mutant form of prelamin A, known as Progerin, resulting in premature aging. HGPS cells show morphological abnormalities of the nuclear membrane, reduced cell proliferation rates, accumulation of reactive oxygen species (ROS), and expression of senescence markers. Lysophosphatidic acid (LPA) is a growth factor‐like lipid mediator that regulates various physiological functions via activating multiple LPA G protein‐coupled receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…LPA signaling through LPAR3 increased expression levels of antioxidant enzymes, consequently inhibiting ROS accumulation and ameliorating cell senescence. Moreover, in a zebra sh model, LPA3 de ciency was su cient to cause premature aging phenotypes in multiple organs as well as a shorter lifespan (58). These results suggest that LPA or LPAR subtypes might exert signi cant positive or detrimental effects on neurodegeneration.…”
Section: Discussionmentioning
confidence: 89%
“…LPA signaling through LPAR3 increased expression levels of antioxidant enzymes, consequently inhibiting ROS accumulation and ameliorating cell senescence. Moreover, in a zebra sh model, LPA3 de ciency was su cient to cause premature aging phenotypes in multiple organs as well as a shorter lifespan (58). These results suggest that LPA or LPAR subtypes might exert signi cant positive or detrimental effects on neurodegeneration.…”
Section: Discussionmentioning
confidence: 89%
“…This mutant line carries a 2 bp deletion (∆CA) and its corresponding protein was truncated and reduced from 353 to 135 amino acid residues ( Figure A1). This lpar3 KO fish displays an aging phenotype and was reported in our previous publication [37]. In this study, we aimed to explore the potential new function of the lpar3 gene on behaviors.…”
Section: Lpar3 Ko Zebrafish Larvae Demonstrated Locomotor Hyperactivitymentioning
confidence: 82%
“…Therefore, LPAR3 may participate in the process to provide a novel treatment for promoting erythropoiesis [55]. In addition, LPAR3 has also been reported to play a role in embryo implantation and spacing in mice [56], mediate chemotaxis of immature murine dendritic cells to unsaturated LPA [57], regulate cellular functions during tumor progression in pancreatic cancer cells [58], and modulate the aging process [37].…”
Section: Discussionmentioning
confidence: 99%
“…Our test results of SOD and MDA found that SMCs in different dose groups can increase the SOD value of cells treated with ox-LDL and decrease the MDA value. SOD and MDA are classic indicators of oxidative stress evaluation, and there are currently reports in the literature that oxidative stress can promote cellular senescence [42][43][44]. Studies show that oxidative stress accelerate telomere shortening or dysfunction and telomere shortening suppresses cancer by triggering senescence in normal cells [45][46][47].…”
Section: Discussionmentioning
confidence: 99%